Role of addiction in motorcycle accidents in MashhadBackground - Araghi, E; Vahedian, M (Advances in Nursing & Midwifery, 2008)
Background Today, governmets pay heavy costs to fight drug abuse. There is a long history of abuse in Iran and, according to WHO, Iran has the first rank in traffic accidents. Purpose This descriptive research was done to determine addiction role in motorcycle accidents in Mashhad Methods 400 bikers experiencing accident and referred to Shaheed Kamyab Hospital (a major trauma center in Mashad) were selected according to inclusion criteria. They were hospitalized at different wards during 2005. A questionnaire completed by interveiw, an observational checklist and medical records were used for data collection. Results Findings showed that most subjects were men between 21 and 30. 17.3% of them had a history of drug abuse mostly opium by smoking and inhalation. 33% of them were cigarette smokers and 25% drank alcohol. Most injures were on extremities. There was a significant relationship between sex, work shift, kinds of safety devices, drug abuse as well as mortality and kinds of damage but no significant relationship was found between transportation quality to hospital as well as accident types and injuries. Conclusion Findings showed that using drugs, alcohol and cigarette was relatively prevalent among injured bikers, which is a predisposing factor in accidents. Thus, preventing this type of use is crucial. Improving knowledge, cultural beliefs, and safe alternative recreational activities, legislating strict laws and controlling borders are ways to restrict tendency to addiction and the resultant reduction of accidents. Keywords Addiction, Accidents, Motorcycle.